Voriconazole exposure and the risk of cutaneous squamous cell carcinoma in allogeneic hematopoietic stem cell transplant patients. Issue 2 (April 2015) - Wojenski, D.J.; Bartoo, G.T.; Merten, J.A.; Dierkhising, R.A.; Barajas, M.R.; el‐Azhary, R.A.; Wilson, J.W.; Plevak, M.F.; Hogan, W.J.; Litzow, M.R.; Patnaik, M.M.; Wolf, R.C.; et al.
Abstract: Background: Voriconazole is a commonly used antifungal medication in allogeneic hematopoietic stem cell transplantation (allo‐HSCT) patients. In solid organ transplantation, voriconazole use has been associated with the development of cutaneous squamous cell carcinoma (SCC). We sought to determine if voriconazole use was associated with SCC in patients undergoing allo‐HSCT. Methods: We retrospectively reviewed consecutive adult patients who underwent allo‐HSCT at Mayo Clinic from January 2007 through July 2012. Multivariable Cox models were created to assess the relationship of SCC with two time‐dependent voriconazole exposure variables: (i) history of voriconazole exposure (yes/no), and (ii) cumulative days of voriconazole use. Results: In our cohort of 381 allo‐HSCT patients, SCC developed in 26 of 312 patients exposed to voriconazole (25 post‐voriconazole) and in 1 of 69 patients who received alternative antifungal agent(s). Cumulative incidence of SCC was estimated to be 19% at 5 years post allo‐transplant. Cumulative days of voriconazole use was found to be a risk factor for SCC, and this relationship persisted in a multivariable model using previously identified risk factors as covariates (hazard ratio 1.859 for each 180 days of use, P  < 0.001). Conclusion: This is the first study, to our knowledge, to identify cumulative days of voriconazole use as a risk factor for SCC development following allo‐HSCT, and may help guide appropriate antifungal use in this patient population.